The Convergent Evolution of Romania's Gross Domestic Product in Relation to the Average Macro-Economic Result of the European Union Countries - Raluca Necula; Mirela Stoian; Manea Drăghici (Amfiteatru Economic Journal, 2016)
Romania's economic growth is a target that can be achieved only within the accordance of all the economic sectors with the Europe 2020 Strategy. As provided in the Convergence Programme 2014-2020, this objective entails a series of steps that Romania must rigorously follow in order to be able to ensure a real converge process at the level of developed European Union (EU) countries form the Euro Area. This paper aims an overview presentation of the economy synthetized in its major result, respectively in the dynamics of the total Gross Domestic Product (GDP) /capita and agricultural Gross Domestic Product (GDP) /capita, and it also compares with the level of the EU 28 average and the level of the Euro Area average. There are calculated, using linear and quadratic functions, the Gross Domestic Product GDP trends, and, with the convergence equation, there are calculated the years that separate Romania from the level of other countries, through the application of annual growth rates. The calculations result shows a strong economic boost of Romania, the annual growth rates being high, both for Gross Domestic Product (GDP) / capita (US) and for agricultural Gross Domestic Product (GDP)/ capita (US), but also a pretty big gap between its development level and the EU 28 and the Euro Area average level.
Keywords: O11; O13; O57; C13; C15; 330; Gross Domestic Product (GDP); trend; comparison; convergence; Romania; European Union (EU); Euro Area